Perioperative and long‐term outcomes of Ross versus mechanical aortic valve replacement. Issue 10 (21st August 2022) - Wenos, Chelsea D.; Herrmann, Jeremy L.; Timsina, Lava R.; Patel, Parth M.; Fehrenbacher, John W.; Brown, John W.
Abstract: Background: The ideal aortic valve replacement strategy in young‐ and middle‐aged adults remains up for debate. Clinical practice guidelines recommend mechanical prostheses for most patients less than 50 years of age undergoing aortic valve replacement. However, risks of major hemorrhage and thromboembolism associated with long‐term anticoagulation may make the pulmonary autograft technique, or Ross procedure, a preferred approach in select patients. Methods: Data were retrospectively collected for patients 18–50 years of age who underwent either the Ross procedure or mechanical aortic valve replacement (mAVR) between January 2000 and December 2016 at a single institution. Propensity score matching was performed and yielded 32 well‐matched pairs from a total of 216 eligible patients. Results: Demographic and preoperative characteristics were similar between the two groups. Median follow‐up was 7.3 and 6.9 years for Ross and mAVR, respectively. There were no early mortalities in either group and no statistically significant differences were observed with respect to perioperative outcomes or complications. Major hemorrhage and stroke events were significantly more frequent in the mAVR population ( p < .01). Overall survival ( p = .93), freedom from reintervention and valve dysfunction free survival ( p = .91) were equivalent. Conclusions: In this mid‐term propensity score‐matched analysis, the Ross procedure offers similar perioperative outcomes, freedom from reintervention or valve dysfunction as well as overall survival compared to traditional mAVR but without the morbidity associated with long‐term anticoagulation. At specialized centers with sufficient expertize, the Ross procedure should be strongly considered in select patients requiring aortic valve replacement.